Bring only the most Beautiful: Towards Excellence in Adult Education - Airini & Pale Sauni (Adult Education Research Conference, 2004)
Adult learners deserve to be taught by excellent educators. This paper identifies information needs about excellence in adult education pedagogy, a model for excellence, case study, and possible ‘next steps’. The analysis arises from New Zealand citizens of Pacific Nation heritage, intentionally expanding mainstream adult education paradigms.